Properties of pertussis toxin B oligomer assembled in vitro from recombinant polypeptides produced by Escherichia coli. - Burnette, W N (1992)
The subunits that make up the pentameric B oligomer of pertussis toxin (S2, S3, S4, and S5) were individually synthesized as recombinant polypeptides in Escherichia coli, isolated as insoluble inclusion bodies, and assembled into a multimeric form in vitro by spontaneous association following treatment with a chaotropic agent, reduction, and reoxidation. The recombinant B multimer, purified by fetuin-Sepharose affinity chromatography, contained all four of the individual subunits and possessed the mitogenic and hemagglutinating activities characteristic of the native B oligomer. Immunization of mice with the recombinant B oligomer elicited antibodies that neutralized pertussis toxin in vitro and, moreover, provided protection in vivo against the leukocytosis-promoting activity of the toxin. These results demonstrate the potential for assembly of complex multimeric proteins from recombinant DNA-derived polypeptides and provide a novel means for production of an acellular pertussis vaccine component.